ANALISIS KELAYAKAN EKONOMI PEMBANGUNAN JALAN KRUENG MANE - BUKETRATA DENGAN CONSUMER SURPLUS - Amirullah Amirullah; Sofyan M. Saleh; Renni Anggraini (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: The national road in North Aceh District is very buzy, especially roads that pass through the Vital Project of Lhokseumawe and its surrounding areas are now called Special Economic Zones (SEZ) Lhokseumawe. Because it's built the way evasion from Krueng Mane to Buketrata along 32 Km, but this road is not perfect yet, especially at the STA 14+750 to STA 21+400. The current reasearch aims to determine the value of time and the Vehicle Operating Costs (VOC); and economic feasibility in Benefit Cost Ratio (BCR), Net Present Value (NPV), and Economic Internal Rate of Return (EIRR) aspects. This study uses a productivity method to calculate the value of time, and the Pacific Consultant International method for calculating the VOC; and Bina Marga method was used to determine the economic feasibility in BCR, NPV, and EIRR aspects. The results of this research shown that daily traffic volume of the annual average (LHRT) on alternative road obtained 9,583 vehicles /day in 2017; the difference in total time value was obtained Rp87,788.- /vehicle and the difference BOK is Rp3,289.- /vehicle; and economic feasibility of the alternative road construction in North Aceh Regency was obtained in 2026. EIRR’s value obtained was at a discount rate of 13.51%, this indicates that the alternative road construction was very feasible to develop with bank lending rates up to 13.51%.Abstract: The national road in North Aceh District is very buzy, especially roads that pass through the Vital Project of Lhokseumawe and its surrounding areas are now called Special Economic Zones (SEZ) Lhokseumawe. Because it's built the way evasion from Krueng Mane to Buketrata along 32 Km, but this road is not perfect yet, especially at the STA 14+750 to STA 21+400. The current reasearch aims to determine the value of time and the Vehicle Operating Costs (VOC); and economic feasibility in Benefit Cost Ratio (BCR), Net Present Value (NPV), and Economic Internal Rate of Return (EIRR) aspects. This study uses a productivity method to calculate the value of time, and the Pacific Consultant International method for calculating the VOC; and Bina Marga method was used to determine the economic feasibility in BCR, NPV, and EIRR aspects. The results of this research shown that daily traffic volume of the annual average (LHRT) on alternative road obtained 9,583 vehicles /day in 2017; the difference in total time value was obtained Rp87,788.- /vehicle and the difference BOK is Rp3,289.- /vehicle; and economic feasibility of the alternative road construction in North Aceh Regency was obtained in 2026. EIRR’s value obtained was at a discount rate of 13.51%, this indicates that the alternative road construction was very feasible to develop with bank lending rates up to 13.51%.